Does an Android-Based Interactive Flipbook Affect the Student’s Science Concept Mastery? - W. M. Nisa; R. A. Tyas (Universitas Negeri Yogyakarta, 2022)
This study aims to determine the effect of using android-based interactive flipbook media in increasing the mastery of science concepts for junior high school students. The research was conducted in one experimental class and one control class at SMP Negeri 2 Genteng, Banyuwangi. The instruments used were 10 multiple choice questions and 3 essay question with cognitive levels of C1 – C6. The method used is a Quasy Experiment with a pretest posttest control group design. The experimental class and control class were taken by simple random sampling. The data analysis technique used is the analysis of the independent sample T test with the help of SPSS application and the standard gain value using the gain equation. Sig value. (2-tailed) independent sample T test is 0.000, this indicates that there is a significant didfference between the average concept matery of student in the experimental class and control class. Gain value shows that the average mastery of the concepts of experimental class student has increased from before and after treatment of 0.66 with moderate criteria. The average concept mastery of control class students increased from before and after treatment by 0.24 with low criteria.